The Role of Water in the Transmission of Healthcare-Associated Infections: Opportunities for Intervention through the Environment. (October 2013) - Denham, Megan E.; Kasali, Altug; Steinberg, James P.; Cowan, David Z.; Zimring, Craig; Jacob, Jesse T.
OBJECTIVE: To assess and synthesize available evidence in the infection control and healthcare design literature on strategies using the built environment to reduce the transmission of pathogens in water that cause healthcare-associated infections (HAIs). BACKGROUND: Water can serve as a reservoir or source for pathogens, which can lead to the transmission of healthcare-associated infections (HAIs). Water systems harboring pathogens, such as Legionella and Pseudomonas spp., can also foster the growth of persistent biofilms, presenting a great health risk. TOPICAL HEADINGS: Strategies for interrupting the chain of transmission through the built environment can be proactive or reactive, and include three primary approaches: safe plumbing practices (maintaining optimal water temperature and pressure; eliminating dead ends), decontamination of water sources (inactivating or killing pathogens to prevent contamination), and selecting appropriate design elements (fixtures and materials that minimize the potential for contamination). CONCLUSIONS: Current evidence clearly identifying the environment's role in the chain of infection is limited by the variance in surveillance strategies and in the methods used to assess impact of these strategies. In order to optimize the built environment to serve as a tool for mitigating infection risk from waterborne pathogens—from selecting appropriate water features to maintaining the water system—multidisciplinary collaboration and planning is essential.